Engineering Interactive Systems 2008 - Forbrig, Peter (Springer, 2017)
This book constitutes the combined proceedings of the second working conference on Human-Centred Software Engineering (HCSE 2008) and the 6th International Workshop on TAsk MOdels and DIAgrams (TAMODIA 2008); jointly held as EIS 2008, the international event on Engineering Interactive Systems, in Pisa, Italy, in September 2008.